Is construction labor productivity really declining?. - Rojas, Eddy M. (Journal of construction engineering and management)
Microeconomics data suggest that labor productivity declined significantly in the construction industry during the 1979-1998 period. However, microeconomic studies indicates the contrary. This paper criticially examines the construction labor productivity macroeconomic data in the United States from 1979 to 1998 to determine their validity and reliability. Data collection, distribution, manipulation, analysis, and interpretation are reviewed and problems are identified. The paper also presents a comparison of construction and manufacturing labor productivity during this period. The main conclusion of the study is that the raw data used to calculate construction productivity values at the macroeconomic level and their further manipulation and interpretation present so many problems that the results should be deemed unreliable. The uncertainty generated in the process of computing these values is such that it cannot be determined if labor productivity has actually increased, decreased, or remained constant in the construction industry for the 1979-1998 period.